Assessing National and Military Security of Russia: Established Procedure and How to Improve It - S. P. Belokon’ (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
This paper examines established procedure of assessing national and military security of the Russian Federation and outlines ways how to improve it. The author unveils deficiencies of the current set of indicators for measuring national and military security of the Russian Federation established by existing legal provisions. He argues that a methodological framework of assessing military security developed by the 46th Central Research and Development Institute of the Ministry of Defense of the Russian Federation can provide a basis for exploring these issues since it allows to harmonize specific methodologies, models and computational tasks, to evaluate the results and to produce generalized assessments of progress in the development of military establishment of the Russian Federation. The paper examines how this methodological framework addresses both a ‘direct’ computational task (forecasting level of military security of the Russian Federation depending on the parameters of the national military establishment), and a ‘reverse’ computational task (setting a target level of military security and defining the parameters of the national military establishment capable of ensuring military security of the Russian Federation over certain time horizon while taking into account anticipated constraints in country’s resource capabilities). The author concludes that a further improvement of methodology for assessing military security as a critical element of national security implies development of an indicator-based approach meant to facilitate making a rational choice of an optimal option for ensuring military security of the Russian Federation. One part of the solution could be a mathematical modelling of a decision-making process and a formalization of a target level of military security on the basis of a fuzzy set theory.